The effects of different exercise loads in plyometric resistance training on respiratory and hormonal levels in female volleyball players - Kavuran, Korhan; Tizar, Ercan; Oral, Diclehan; Erdogan, Ramazan; Celikel, Baha Engin; Ceylan, Tulay; Karatas, Baykal (Frontiers Media Sa, 2025)
Background The present study set out to ascertain the effects of combined exercises, consisting of resistance training and plyometric exercises at varying degrees of intensity, on biochemical and respiratory parameters in female volleyball players.Methods The research group consisted of 20 professional female volleyball players who participated in national and international volleyball competitions. Participants were randomly divided into two groups: a control group (n = 10) that performed low-intensity exercises at 30%-50% intensity, and an experimental group (n = 10) that followed a high-intensity exercise programme at 60%-80% intensity. Blood samples and spirometric respiratory function values were collected before and after the 8-week exercise program. The biochemical analyses included the assessment of luteinizing hormone (LH), growth hormone (GH), insulin-like growth factor-1 (IGF-1), and total iron binding capacity. Respiratory function was analysed using forced vital capacity (FVC), forced expiratory volume in one second (FEV1), and forced expiratory flow at mid-expiration (FEF). The data were analysed using the SPSS statistical package.Results The results demonstrated a decline in IGF-1, GH, and total iron-binding capacity levels, and an increase in LH levels, in the biochemical parameters of the control group. Additionally, FVC, FEV1, and FEF values exhibited an increase in the control group. Conversely, the experimental group demonstrated a significant increase in LH, GH, IGF-1, and total iron-binding capacity levels. With regard to respiratory parameters, an increase in FEF values was observed, whilst FVC and FEV1 values decreased. The present findings suggest that high-intensity plyometric resistance exercises have more pronounced effects on biochemical responses, but may trigger different adaptation mechanisms in respiratory capacit. The results of the study showed that there was a difference between the control group's GH, IGF-1, FVC, and FEV1 data and the experimental group's GH, IGF-1, FVC, and FEV1 data.Conclusions In conclusion, plyometric resistance exercises at varying intensities influence both respiratory and biochemical parameters in female volleyball players. Accordingly, well-planned and individualised plyometric resistance training programmes are thought to enhance both the health and athletic performance of athletes.
Keywords: sports; post-activation performance enhancement; jump performance; voleyball; strength training resistance